SIMPLIFIED METHOD FOR CALCULATING CLOSING IN OF SWITCH-GEAR FLEXIBLE BUSES AT SHORT CIRCUIT BY IMPULSE OF ELECTRODYNAMIC FORCES - I. I. Sergey; E. G. Ponomarenko; W. M. Sammur; P. I. Klimkovich (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper contains description of a simplified method for calculating closing-in of switch-gear flexible buses at short circuit. The developed method is based on integral and energy principles of  mechanics. In order to increase accuracy of the calculation corrections factors are introduced in an explicit formula for calculation of maximum horizontal deviations. These factors have been obtained with the help of a computer program that realized numerical method for calculating closing-in of wires by flexible thread levels.Diagrams are constructed with the purpose to find ymax and criteria of electro-dynamic resistance of flexible buses (permissible impulse of electro-dynamic forces and current of electro-dynamic resistance) is determined.